2018
DOI: 10.1007/s00345-018-2439-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative sensitivity and specificity of imaging modalities in staging bladder cancer prior to radical cystectomy: a systematic review and meta-analysis

Abstract: MRI and PET/CT provides superior sensitivity compared to CT for detection of positive lymph nodes in bladder cancer prior to cystectomy. There is variability in the accuracy that current imaging modalities achieve across different studies. A number of other factors impact on detection accuracy and these must be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 48 publications
0
39
2
1
Order By: Relevance
“…In a combined meta-analysis and single-institution study of patients with bladder cancer scheduled to undergo radical cystectomy and pelvic lymph node dissection, the authors determined that the pooled sensitivity and specificity for detection of lymph node metastases were 57% and 95%, respectively [52]. These findings were also confirmed in two subsequent meta-analyses, which demonstrated a pooled sensitivity of 56-57% and a pooled specificity of 92% for the detection of lymph node metastases on FDG-PET/CT [53,54]. A small (n = 15) study evaluating the use of FDG-PET/CT for the preoperative lymph node staging of MIBC demonstrated minimal benefit of FDG-PET/CT compared with CT alone, thought to potentially be due to overlap in standardized uptake values (SUVs) between inflammatory and malignant lesions [55].…”
Section: Fdg-pet/ct For Bladder Cancer Stagingmentioning
confidence: 86%
“…In a combined meta-analysis and single-institution study of patients with bladder cancer scheduled to undergo radical cystectomy and pelvic lymph node dissection, the authors determined that the pooled sensitivity and specificity for detection of lymph node metastases were 57% and 95%, respectively [52]. These findings were also confirmed in two subsequent meta-analyses, which demonstrated a pooled sensitivity of 56-57% and a pooled specificity of 92% for the detection of lymph node metastases on FDG-PET/CT [53,54]. A small (n = 15) study evaluating the use of FDG-PET/CT for the preoperative lymph node staging of MIBC demonstrated minimal benefit of FDG-PET/CT compared with CT alone, thought to potentially be due to overlap in standardized uptake values (SUVs) between inflammatory and malignant lesions [55].…”
Section: Fdg-pet/ct For Bladder Cancer Stagingmentioning
confidence: 86%
“…Finally, the accuracy of mpMRI in nodal staging was not assessed in the present study, limiting its applicability as a comprehensive staging tool. However, a recent metaanalysis showed that MRI and PET/CT have a comparable performance in nodal staging [24].…”
Section: Discussionmentioning
confidence: 99%
“…MRI and (PET/CT) provides superior sensitivity compared to CT for the detection of positive LN in BC before cystectomy. There is variability in the accuracy that current imaging modalities achieve across different studies [ 10 ]. Combining metabolical and morphological features using 18F-FDG PET/CT improves the detection of malignant LN in patients with BC [ 11 ].…”
Section: Discussionmentioning
confidence: 99%